Knowledge of ethnic minorities in the central highlands region of Vietnam – viewed from development resources - Duc, Tran Minh (Technium Sustainability, 2024)
Over the last few decades, when researching ethnic minority communities, researchers have increasingly focused on the local knowledge assets that the community has amassed through productive labour and life organisation. The Central Highlands is a multi-ethnic area that still retains various and distinct sources of traditional knowledge, which play a crucial role in the community’s long-term development. Based on the materials gathered, the paper primarily examines the function of indigenous knowledge as a development resource in the Central Highlands region.